Volar Radiocarpal Ligament Repair with Suture Anchors for Radiocarpal Fracture Dislocations: Case Series - Bohm, Kyle C.; Geissler, Jacqueline; Ward, Christina M. (Journal of Wrist Surgery, 2020)
Background Radiocarpal fracture dislocations cause significant intraarticular disruption and instability difficult to treat with traditional plating methods.Description of Technique Suture anchor fixation of the volar radiocarpal ligaments through an extended carpal tunnel approach, supplemented with radial styloid fixation, restores stability to the radiocarpal joint.Patients and Methods We performed a retrospective review of 14 consecutive radiocarpal fracture-dislocations (RCFDs) treated at two-level one trauma center from 2011 to 2015. In all cases, the volar radiocarpal ligaments were repaired to the distal radius with suture anchors.Results We reviewed 14 Dumontier Group 2 RCFDs in 14 patients (10 males, four females) with an average age of 39 years (range 22–53 years). Final follow-up averaged 288 days (range 7–1,364 days). Surgeons performed volar ligament repair with suture anchors in all cases, radial styloid fixation in 79% (11/14), and dorsal plate fixation in 29% (4/14). Eight of 14 patients (57%) had a “flipped” volar lip fragment of the distal radius. Three patients had forearm compartment syndrome and two patients had acute carpal tunnel syndrome. No patients experienced radiocarpal subluxation after volar ligament repair.Conclusion No recurrent subluxation or dislocation occurred after primary repair of the volar radiocarpal ligaments using suture anchors in this series of radiocarpal fracture dislocations. Volar radiocarpal ligament repair also addressed the “flipped” volar rim fragment that could not be addressed through a dorsal approach alone.Level of Evidence: This is a Level IV, case series therapeutic study.
Keywords: distal radius fracture; ligament repair; radiocarpal dislocation